Pengaruh Lifestyle dan Quality Product terhadap Brand Switching dengan Variety Seeking sebagai Variabel Moderasi pada Peralihan Smartphone Android ke Iphone - Nugroho, Moch. Andre; Badi’ah, Roudlotul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study involved 100 respondents to examine the influence of lifestyle and product quality on brand switching, with variety seeking as a moderating variable. Primary data was collected through interviews and questionnaires. Data analysis was performed using SmartPLS 3, which includes outer model analysis, inner model analysis, and hypothesis testing. The findings indicate that the model shows adequate validity and reliability. Hypothesis testing reveals that both lifestyle and product quality have a significant positive effect on brand switching, meaning that consumers' preferences for lifestyle and high-quality products encourage them to switch brands. Additionally, variety seeking also has a significant positive effect on brand switching, indicating that consumers seek variety when choosing brands. However, variety seeking does not moderate the relationship between lifestyle and product quality with brand switching, meaning that while variety seeking influences brand switching, it does not strengthen or weaken the impact of lifestyle or product quality on this behavior. The implications of these results suggest that brands should focus on aligning their products with consumers' lifestyles and ensuring high product quality to drive brand switching.